Fatigue prediction of high-strength bolts in wind turbines - Zheng Qishan; Zhu Shaohong; Chen Changhong; Chang Haiqing; Yan Xizhong; Wei Chenxi (Dianzi Jishu Yingyong, 2024)
The flange plate and blade root hub of wind turbines are connected by high-strength bolts, and the collapse of most wind turbine towers is caused by the fatigue of the connecting bolts. In order to reduce the occurrence of such tower collapse accidents, a new method for analyzing and predicting bolt fatigue damage is proposed. For high-strength connecting bolts of 2.0 MW wind turbine generators, ultrasonic probes and temperature sensors are used to collect bolt data and obtain random stress spectra of the bolts. Then the stress spectrum is modified based on the rain flow counting method and Goodman formula, and the stress cycle data are extracted. Finally, based on the S-N curve of bolt material and Miner's linear cumulative damage theory, a bolt fatigue prediction model is constructed. The experimental results show that the estimated bolt fatigue damage is far less than the bolt fatigue limit, which meets the design life requirements of the wind turbine.